Antimicrobial Activity of the Peptide LfcinB15 against Candida albicans - Chang, Che-Kang (J Fungi (Basel), 2021)
Lactoferricin (Lfcin) is an amphipathic, cationic peptide derived from proteolytic cleavage of the N-lobe of lactoferrin (Lf). Lfcin and its derivatives possess broad-spectrum antibacterial and antifungal activities. However, unlike their antibacterial functions, the modes of action of Lfcin and its derivatives against pathogenic fungi are less well understood. In this study, the mechanisms of LfcinB15, a derivative of bovine Lfcin, against Candida albicans were, therefore, extensively investigated. LfcinB15 exhibited inhibitory activity against planktonic cells, biofilm cells, and clinical isolates of C. albicans and non-albicans Candida species. We further demonstrated that LfcinB15 is localized on the cell surface and vacuoles of C. albicans cells. Moreover, LfcinB15 uses several different methods to kill C. albicans, including disturbing the cell membrane, inducing reactive oxygen species (ROS) generation, and causing mitochondrial dysfunction. Finally, the Hog1 and Mkc1 mitogen-activated protein kinases were both activated in C. albicans cells in response to LfcinB15. These findings help us to obtain more insight into the complex mechanisms used by LfcinB15 and other Lfcin-derived peptides to fight fungal pathogens.